Hungarian Magazines for Children, 1900-1940. The Case of Two Contemporary Journals - Szabolcs, Éva (Rivista di Storia dell’Educazione, 2017)
The article focuses on presenting two interwar children’s magazines in Hungary. It is evident to see how the education and socialization of children and youth took place on the pages of these journals. Referring to the theory of the social construction of childhood these magazines represent a culturally defined childhood in a discourse of interwar Hungary. In these magazines the educative purpose dominated but in the 1920-30s the intention of children’s amusement became present in the analyzed journals.